Design of Solar Power Plant for Electricity Source of The Drying Machine - Uais Sabilah Muhammad; Bambang Purwahyudi (JEECS (Journal of Electrical Engineering and Computer Sciences), 2021)
The increasing demand for electrical energy and the development of power generation technology have caused to the development of micro-scale industries increasing in Indonesia. The development of this micro-scale industries are expected to be able to utilize electrical energy from solar panels as the main source of electrical energy. In this paper, solar panels are used as a source of electrical energy in the drying machine. Utilization of solar panels aims to reduce production costs where solar energy is absorbed through solar panel as the main source of electrical energy for drying machine. In addition, the use of solar energy aims to make the drying machine continuously operate. This drying machine uses a heater of 700Watt and is operated during 4 hours. From the calculation results of the solar power plant system design are obtained the capacity battery of 300 Ah, the capacity solar cells of 10x100 Wp, the capacity inverter of 700 watt and the Solar Charger Controller (SCC) of 60 amperes.